A novel approach to measure mitochondrial respiration in frozen biological samples. (20th May 2020) - Acin‐Perez, Rebeca; Benador, Ilan Y; Petcherski, Anton; Veliova, Michaela; Benavides, Gloria A; Lagarrigue, Sylviane; Caudal, Arianne; Vergnes, Laurent; Murphy, Anne N; Karamanlidis, Georgios; Tian, Rong; Reue, Karen; et al.
Abstract: Respirometry is the gold standard measurement of mitochondrial oxidative function, as it reflects the activity of the electron transport chain complexes working together. However, the requirement for freshly isolated mitochondria hinders the feasibility of respirometry in multi‐site clinical studies and retrospective studies. Here, we describe a novel respirometry approach suited for frozen samples by restoring electron transfer components lost during freeze/thaw and correcting for variable permeabilization of mitochondrial membranes. This approach preserves 90–95% of the maximal respiratory capacity in frozen samples and can be applied to isolated mitochondria, permeabilized cells, and tissue homogenates with high sensitivity. We find that primary changes in mitochondrial function, detected in fresh tissue, are preserved in frozen samples years after collection. This approach will enable analysis of the integrated function of mitochondrial Complexes I to IV in one measurement, collected at remote sites or retrospectively in samples residing in tissue biobanks. Synopsis: Freeze‐thawing events cause mitochondrial membrane permeabilization and disrupt mitochondrial functionality in cells and tissues. Reconstitution of maximal mitochondrial respiration allows the analysis of mitochondrial bioenergetics in frozen and thawed crude samples, thus overcoming limitations associated with the current methods. Following reconstitution, mitochondrial maximal respiration can be assessed in frozen isolated mitochondria or total tissue lysate. Respiratory rate measurements from tissue lysates reduce by an order of magnitude the minimal mass of tissue required. Maximal respiration rates in reconstituted frozen samples are comparable to those in fresh ones. Respiratory rates can be normalized per cell, per total protein or per mitochondrial content in frozen specimens. Respiratory rates can be measured in stored samples from clinical and animal studies, and drug toxicity assays. Abstract : Reconstitution of maximal mitochondrial respiration circumvents the limitations associated with current methods for assessing mitochondrial bioenergetics in frozen clinical samples.